SIKAP DAN POLA PEMBELIAN BUMBU INSTAN KEMASAN OLEH KONSUMEN RUMAH TANGGA DI BANDAR LAMPUNG - Juwita, Aria; Sayekti, Wuryaningsih Dwi; Indriani, Yaktiworo (Jurnal Ilmu-Ilmu Agribisnis, 2015)
The purpose of this research were to determine the household consumer attitudes, purchasing patterns, and the dominant affecting factor of the instant seasoning purchase. This research was conducted in sub-district of Kemiling and Rajabasa of Bandar Lampung City. The number of 67 households was drawn by the method of group stages sampling.  The research data was analyzed by Fishbein and principal component analysis. The result showed that the pattern of instant seasoning purchases by consumers in Bandar Lampung as follows: the average purchase frequency of instant seasoning was twice per month, 3-4 sachet purchase amount, and the type of instant seasoning most preferred by consumers were racik tempe and fried rice. The most preferred and trusted attributes by consumers were the ease of obtaining the product, expired date information and the taste. Based on the score of attitude attributes on instant seasoning, the brand of Indofood and ease of obtaining the product got the highest score, followed by the attribute expiration information and the taste.  The dominant factor on influencing purchasing decisions of seasoning was formed by four main components (factors) based on the value of the loading factors.  The first component (information) consists of expiration information, others’ influences and composition of the product.  The second component (product) consists of the influence of taste, promotions and prices.  The third component (product suitability) consists of variables brand and conformity with the type of cuisine. The fourth component (ease of obtaining the product) consists of variable ease of obtaining the product. Key words: attitude, factor analysis, instant seasoning